1997
DOI: 10.1097/00004872-199715120-00009
|View full text |Cite
|
Sign up to set email alerts
|

Association between high heart rate and high arterial rigidity in normotensive and hypertensive subjects

Abstract: This study demonstrates that there is a statistically significant positive link between high heart rate and high arterial stiffness measured at the site of central and lower limb arteries. Since an elevated heart rate has been shown to be associated with cardiovascular risk, such findings may be relevant for future cardiovascular studies in epidemiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
142
4
6

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(169 citation statements)
references
References 28 publications
17
142
4
6
Order By: Relevance
“…5,[36][37][38] The effect of heart rate on arterial stiffness is somewhat a controversial issue. In a recent observational study, Sa Cunha et al 23 showed that high heart rate was strongly associated with elevated PWV even after adjustment for age and BP. The increase in heart rate by isoproterenol and pacing was associated with an increase in PWV.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…5,[36][37][38] The effect of heart rate on arterial stiffness is somewhat a controversial issue. In a recent observational study, Sa Cunha et al 23 showed that high heart rate was strongly associated with elevated PWV even after adjustment for age and BP. The increase in heart rate by isoproterenol and pacing was associated with an increase in PWV.…”
Section: Discussionmentioning
confidence: 98%
“…In some studies, PWV was only correlated with SBP, 20,21 but in others with both SBP and DBP. 22 Sa Cunha et al 23 suggested gender difference; SBP showed correlation with PWV in both genders, whereas DBP was correlated with PWV only in women. In contrast to the previous studies, Nurnberger et al 18 reported that DBP was an only important haemodynamic determinant of PWV in young healthy males.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 The relationship between heart rate and blood pressure has been established in large cohorts of unselected subjects. 9 Sa Cunha et al 11 have shown that pulse wave velocity and casual heart rate at rest were positively correlated in normotensive and hypertensive patients. The same authors have also shown that ambulatory heart rate is related to pulsatile changes in the diameter of the carotid artery.…”
Section: Introductionmentioning
confidence: 98%
“…22,25 Others found that PWV was correlated to both SBP and DBP 18 or was correlated to SBP in both men and women, but was correlated to DBP only in women. 26 The controversial results reported in the literature may be attributed to the large variability in the population studied, such as the broad age range, gender distribution and the presence of different diseases or drug regimens. Additionally, age-related changes in the vasculature including a widening of pulse pressure, 27 changes in heart rate, blood pressure and vascular resistance 28 may further complicate the evaluation of stiffness determinants.…”
Section: Introductionmentioning
confidence: 99%